Method for synthesizing high-density high-purity silicon carbide

By using layered temperature field distribution and laminated coding methods in graphite crucibles, the size and bulk density of silicon carbide particles have been successfully improved, and the problems of small particles and small pile density in traditional processes have been solved, high-purity and high-efficiency silicon carbide synthesis have been achieved, and production costs have been reduced.

CN119911911APending Publication Date: 2025-05-02HENAN ZHONGYI CHUANGXIN DEV CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411979620.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

After mixing traditional silicon powder particles and carbon powder, silicon carbide is synthesized at high temperature through self-propagation method. The particles generated are small, needle-shaped SiC is slender, and the bulk density is not large, making it difficult to meet the demand for large-grained silicon carbide in high-tech fields such as third-generation semiconductors.

Method used

Using graphite crucibles and vacuum synthesis furnaces, the temperature field distribution is changed by opening holes at the bottom of the graphite carbon felt. The layered temperature field distribution is conducive to the formation of large-grain powders. Weigh high-purity Si powder and thin graphite paper according to a certain stoichiometric ratio, and then stack and pack it in a vacuum synthesis furnace for high-temperature synthesis, and control the temperature of each area for insulation operation.

Benefits of technology

The resulting silicon carbide particles are large, full and dense, with a purity of more than 99.99995%. The particle size of a single furnace is 0.4mm and the coarse content is increased by more than 25%. At the same time, graphite paper can be recycled to reduce production costs and improve economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119911911A_ABST
    Figure CN119911911A_ABST
Patent Text Reader

Abstract

The invention relates to a method for synthesizing high-density and high-purity silicon carbide, which comprises the following steps of: weighing high-purity Si powder and thin graphite paper according to a certain stoichiometric ratio, spreading a layer of thin Si powder and spreading a layer of thin graphite paper for stacking until the whole graphite crucible is full, putting the graphite crucible loaded with a mixture of the high-purity Si powder and the thin graphite paper into a vacuum synthesis furnace, and carrying out vacuum synthesis on the high-density and high-purity silicon carbide. Closing the furnace cover, and after vacuumizing, filling inert gas to the required pressure intensity; uniformly dividing the crucible into four areas from top to bottom, heating according to a certain heating rate, controlling the temperature of each area, and simultaneously carrying out heat preservation operation so as to carry out high-temperature synthesis; and after a period of time, the required silicon carbide powder can be obtained. According to the method, the operation difficulty is low, generated silicon carbide particles are large, full and high in stacking density, the used graphite paper is recycled, silicon carbide is regenerated, waste is turned into wealth, the production cost is greatly reduced, and compared with the prior art, the method has good market prospects and development space.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-purity silicon carbide powder synthesis, and in particular to a method for synthesizing high-density and high-purity silicon carbide. Background Art

[0002] Electronic grade silicon carbide powder particles are extremely pure, uniform in size and have specific physical and chemical properties. It has important applications in high-tech fields such as semiconductor manufacturing. The purity of the electronic grade silicon carbide produced by our company is above 99.9999%, and the product value is very high. However, the traditional process uses small silicon particles with a particle size of 1-2mm and carbon powder with a particle size of 30-50 microns. The synthesized silicon carbide particles are small and have a low packing density. In the crystal growth process, high-density large-particle silicon carbide is preferred. Therefore, in the synthesis of third-generation semiconductor silicon carbide powder, high-purity electronic grade silicon carbide with large particles and high packing density has become a technical problem to be overcome.

[0003] The traditional silicon powder particles and carbon powder are mixed and synthesized by the self-propagating method at high temperature. The particles are small, the needle-shaped SiC is slender, and the stacking density is not large. The reason is that the nearby carbon is dissolved in the silicon liquid to generate silicon carbide. Since silicon carbide has no melting point, it grows into small needles through the longitudinal temperature gradient.

[0004] How to design a method that is reasonable and feasible, with ingenious design, good process stability, low operating difficulty, and the generated silicon carbide particles are large, full, and have a high bulk density, and the used graphite paper can be recycled to regenerate silicon carbide, turning waste into treasure, greatly reducing production costs, and improving economic benefits. A method for synthesizing high-density and high-purity silicon carbide is the problem that needs to be solved at present. Summary of the invention

[0005] In order to solve the technical problems that silicon carbide is synthesized by the self-propagating method at high temperature after the existing traditional silicon powder particles and carbon powder are mixed, the particles are small, the needle-shaped SiC is slender, and the packing density is not large, the present invention provides a method for synthesizing high-density and high-purity silicon carbide, so as to achieve the purpose of reasonable and feasible method, ingenious design, good process stability, low operation difficulty, large and full silicon carbide particles generated, high packing density, recycling used graphite paper, regenerating silicon carbide, turning waste into treasure, greatly reducing production costs, and improving economic benefits.

[0006] The technical solution adopted by the present invention to solve the above technical problems is: a method for synthesizing high-density and high-purity silicon carbide, comprising the following steps: Step 1: weigh high-purity Si powder and thin graphite paper according to a certain stoichiometric ratio, first lay a layer of high-purity carbon powder on the bottom of the graphite crucible as a base, then lay a layer of thin graphite paper, and then stack and pack according to sprinkling a layer of thin Si powder and laying a layer of thin graphite paper until the entire graphite crucible is filled; Step 2: Place the graphite crucible containing the mixture of high-purity Si powder and thin graphite paper into a vacuum synthesis furnace, close the furnace cover, and after evacuation, fill it with inert gas to the required pressure; Step 3, dividing the graphite crucible into four equal areas from top to bottom, heating the crucible at a certain heating rate, controlling the temperature of each area, and performing a heat preservation operation at the same time, so as to perform high temperature synthesis; Step 4: Cool down and stop the furnace. After a period of time, the desired silicon carbide powder can be obtained.

[0007] The above is a basic implementation manner of the present invention, and further improvements, perfections and limitations can be made on the above basis: for example, in step 1, the molar ratio of high-purity Si powder and thin graphite paper is 1:1.03-1:1.13; the total weight of the Si powder and thin graphite paper is 30.75-31.5 kg.

[0008] The above is a basic implementation mode of the present invention, and further improvements, perfections and limitations can be made on the above basis: as in the step 1, the thin Si powder can also be stirred with anhydrous alcohol to form a silicon powder slurry, which is coated on the surface of the thin graphite paper. Similarly, a layer of silicon powder slurry is applied and a layer of thin graphite paper is laid for stacking and packing until the entire graphite crucible is filled.

[0009] The above is a basic implementation of the present invention, and further improvements, perfections and limitations can be made on the above basis: for example, the insulation layer arranged in the vacuum synthesis furnace in step 2 is graphite carbon felt, and an aperture is opened at the bottom of the graphite carbon felt, and the aperture size is 15-20 cm.

[0010] The above is a basic implementation of the present invention, and further improvements, perfections and limitations can be made on the above basis: for example, the vacuum pressure in step 2 is 0.5 Pa, and the inert gas is argon.

[0011] The above is a basic implementation of the present invention, and further improvements, perfections and limitations can be made on the above basis: as described in step 3, the first area occupies one quarter of the volume of the crucible, the temperature is controlled at 1950-2100 ° C, and the insulation time is 18-25H; the second area occupies one quarter of the volume of the crucible, the temperature is controlled at 2100-2200 ° C, and the insulation time is 18-25H; the third area occupies one quarter of the volume of the crucible, the temperature is controlled at 2150-2200 ° C, and the insulation time is 18-25H; the fourth area occupies one quarter of the volume of the crucible, the temperature is controlled at 1950-2100 ° C, and the insulation time is 18-25H; The above is a basic implementation manner of the present invention, and further improvements, perfections and limitations can be made on the above basis: for example, the cooling and furnace stopping time in step 4 is 20-30 hours, the silicon carbide powder has a particle size of 0.4 mm and a coarse content of ≥75%, and the purity of the silicon carbide powder is above 99.99995%.

[0012] Compared with the prior art, the present invention has the following beneficial effects: First, the present invention changes the temperature field distribution inside the graphite crucible by opening holes at the bottom of the graphite carbon felt, and changes the traditional annular temperature field distribution into a layered temperature field distribution. This solves the technical problem that the temperature of the annular temperature field distribution is high at the bottom and low at the top, resulting in the powder temperature at the bottom failing to meet the set requirements during the powder synthesis process, thereby failing to continue to sublimate and synthesize large-particle powders.

[0013] Secondly, the present invention controls the temperature distribution of each layer precisely and timely, and the layered temperature field distribution is conducive to the formation of large-particle powder in each layer, thereby increasing the content of large-particle powder as a whole, and the generated silicon carbide particles are large, full, and have a high bulk density.

[0014] Third, the present invention can recycle the used graphite paper to regenerate silicon carbide, turning waste into treasure and improving economic benefits.

[0015] Fourth, the present invention changes the temperature field distribution in the crucible through the carbon felt protective layer structure, increases the synthesis amount of large-particle silicon carbide in each layer, and increases the coarse content of the single-furnace particle size of 0.4 mm by more than 25%. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A schematic diagram of a graphite crucible used in the present invention; In the figure, 1. graphite crucible, 2. graphite crucible cover, 3. silicon powder, 4. recycled graphite paper. DETAILED DESCRIPTION

[0017] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0018] Example 1 A method for synthesizing high-density and high-purity silicon carbide comprises the following steps: Step 1: weigh high-purity Si powder and thin graphite paper according to a certain stoichiometric ratio, first lay a layer of high-purity carbon powder on the bottom of the graphite crucible as a base, then lay a layer of thin graphite paper, and then stack and pack according to sprinkling a layer of thin Si powder and laying a layer of thin graphite paper until the entire graphite crucible is filled; Step 2: Place the graphite crucible containing the mixture of high-purity Si powder and thin graphite paper into a vacuum synthesis furnace, close the furnace cover, and after evacuation, fill it with inert gas to the required pressure; Step 3, dividing the graphite crucible into four equal areas from top to bottom, heating the crucible at a certain heating rate, controlling the temperature of each area, and performing a heat preservation operation at the same time, so as to perform high temperature synthesis; Step 4: Cool down and stop the furnace. After a period of time, the desired silicon carbide powder can be obtained.

[0019] The molar ratio of the high-purity Si powder and the thin graphite paper in the step 1 is 1:1.03; the total weight of the Si powder and the thin graphite paper is 30.75 kg.

[0020] The insulation layer provided in the vacuum synthesis furnace in step 2 is graphite carbon felt, and an aperture is provided at the bottom of the graphite carbon felt, and the aperture size is 15 cm.

[0021] The vacuum pressure in step 2 is 0.5 Pa, and the inert gas is argon.

[0022] In the step 3, the first area occupies one quarter of the volume of the crucible, the temperature is controlled at 1950°C, and the insulation time is 18 hours; the second area occupies one quarter of the volume of the crucible, the temperature is controlled at 2100°C, and the insulation time is 18 hours; the third area occupies one quarter of the volume of the crucible, the temperature is controlled at 2150°C, and the insulation time is 18 hours; the fourth area occupies one quarter of the volume of the crucible, the temperature is controlled at 1950°C, and the insulation time is 18 hours; The cooling and furnace stopping time in step 4 is 20 hours, the particle size of the silicon carbide powder is 0.4 mm and the coarse content is ≥ 75%, and the purity of the silicon carbide powder is above 99.99995%.

[0023] Example 2 A method for synthesizing high-density and high-purity silicon carbide comprises the following steps: Step 1: weigh high-purity Si powder and thin graphite paper according to a certain stoichiometric ratio, first lay a layer of high-purity carbon powder on the bottom of the graphite crucible as a base, then lay a layer of thin graphite paper, and then stack and pack according to sprinkling a layer of thin Si powder and laying a layer of thin graphite paper until the entire graphite crucible is filled; Step 2: Place the graphite crucible containing the mixture of high-purity Si powder and thin graphite paper into a vacuum synthesis furnace, close the furnace cover, and after evacuation, fill it with inert gas to the required pressure; Step 3, dividing the graphite crucible into four equal areas from top to bottom, heating the crucible at a certain heating rate, controlling the temperature of each area, and performing a heat preservation operation at the same time, so as to perform high temperature synthesis; Step 4: Cool down and stop the furnace. After a period of time, the desired silicon carbide powder can be obtained.

[0024] The molar ratio of the high-purity Si powder and the thin graphite paper in the step 1 is 1:1.08; the total weight of the Si powder and the thin graphite paper is 31.1 kg.

[0025] The thermal insulation layer provided in the vacuum synthesis furnace in step 2 is graphite carbon felt, and an aperture is provided at the bottom of the graphite carbon felt, and the aperture size is 18 cm.

[0026] The vacuum pressure in step 2 is 0.5 Pa, and the inert gas is argon.

[0027] In the step 3, the first area occupies one quarter of the volume of the crucible, the temperature is controlled at 2050°C, and the insulation time is 21 hours; the second area occupies one quarter of the volume of the crucible, the temperature is controlled at 2150°C, and the insulation time is 21 hours; the third area occupies one quarter of the volume of the crucible, the temperature is controlled at 2175°C, and the insulation time is 21 hours; the fourth area occupies one quarter of the volume of the crucible, the temperature is controlled at 2050°C, and the insulation time is 21 hours; The cooling and furnace stopping time in step 4 is 25 hours, the particle size of the silicon carbide powder is 0.4 mm and the coarse content is ≥ 75%, and the purity of the silicon carbide powder is above 99.99995%.

[0028] Example 3 A method for synthesizing high-density and high-purity silicon carbide comprises the following steps: Step 1: weigh high-purity Si powder and thin graphite paper according to a certain stoichiometric ratio, lay a layer of high-purity carbon powder on the bottom of the graphite crucible, stir the thin Si powder and anhydrous alcohol into silicon powder slurry, and apply it on the surface of the thin graphite paper. Similarly, apply a layer of silicon powder slurry and a layer of thin graphite paper for stacking and packing until the entire graphite crucible is filled; Step 2: Place the graphite crucible containing the mixture of high-purity Si powder and thin graphite paper into a vacuum synthesis furnace, close the furnace cover, and after evacuation, fill it with inert gas to the required pressure; Step 3, dividing the graphite crucible into four equal areas from top to bottom, heating the crucible at a certain heating rate, controlling the temperature of each area, and performing a heat preservation operation at the same time, so as to perform high temperature synthesis; Step 4: Cool down and stop the furnace. After a period of time, the desired silicon carbide powder can be obtained.

[0029] The molar ratio of the high-purity Si powder and the thin graphite paper in the step 1 is 1:1.13; the total weight of the Si powder and the thin graphite paper is 31.5 kg.

[0030] The thermal insulation layer provided in the vacuum synthesis furnace in step 2 is graphite carbon felt, and an aperture is provided at the bottom of the graphite carbon felt, and the aperture size is 20 cm.

[0031] The vacuum pressure in step 2 is 0.5 Pa, and the inert gas is argon.

[0032] In the step 3, the first area occupies one quarter of the volume of the crucible, the temperature is controlled at 2100°C, and the holding time is 25 hours; the second area occupies one quarter of the volume of the crucible, the temperature is controlled at 2200°C, and the holding time is 25 hours; the third area occupies one quarter of the volume of the crucible, the temperature is controlled at 2200°C, and the holding time is 5 hours; the fourth area occupies one quarter of the volume of the crucible, the temperature is controlled at 2100°C, and the holding time is 25 hours; The cooling and furnace stopping time in step 4 is 30 hours, the particle size of the silicon carbide powder is 0.4 mm and the coarse content is ≥ 75%, and the purity of the silicon carbide powder is above 99.99995%.

[0033] The method of the invention is reasonable and feasible, ingeniously designed, good in process stability, low in difficulty in operation, and the generated silicon carbide particles are large, full, and have a high bulk density. Used graphite paper is recycled to regenerate silicon carbide, turning waste into treasure, greatly reducing production costs, and improving economic benefits. The method solves the technical problems of the existing traditional silicon powder particles and carbon powder being mixed and synthesized by a self-propagating method at high temperature, such as small particles, slender needle-shaped SiC, and low bulk density. Compared with the existing technology, the method has a good market prospect and development space.

[0034] The preferred specific implementation modes and embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above implementation modes and embodiments, and various changes can be made within the knowledge scope of those skilled in the art without departing from the concept of the present invention.

Claims

1. A method for synthesizing high-density and high-purity silicon carbide, characterized in that: The following steps are included: Step 1: weigh high-purity Si powder and thin graphite paper according to a certain stoichiometric ratio, first lay a layer of high-purity carbon powder on the bottom of the graphite crucible as a base, then lay a layer of thin graphite paper, and then stack and pack according to sprinkling a layer of thin Si powder and laying a layer of thin graphite paper until the entire graphite crucible is filled; Step 2: Place the graphite crucible containing the mixture of high-purity Si powder and thin graphite paper into a vacuum synthesis furnace, close the furnace cover, and after evacuation, fill it with inert gas to the required pressure; Step 3, dividing the graphite crucible into four equal areas from top to bottom, heating the crucible at a certain heating rate, controlling the temperature of each area, and performing a heat preservation operation at the same time, so as to perform high temperature synthesis; Step 4: Cool down and stop the furnace. After a period of time, the desired silicon carbide powder can be obtained.

2. A method for synthesizing high-density and high-purity silicon carbide according to claim 1, characterized in that: In the step 1, the molar ratio of the high-purity Si powder to the thin graphite paper is 1:1.03-1:1.13; the total weight of the Si powder and the thin graphite paper is 30.75-31.5 kg.

3. A method for synthesizing high-density and high-purity silicon carbide according to claim 1, characterized in that: The thin Si powder in step 1 can also be stirred with anhydrous alcohol to form a silicon powder slurry, which is then coated on the surface of the thin graphite paper. Similarly, a layer of silicon powder slurry is applied and a layer of thin graphite paper is laid for stacking and packing until the entire graphite crucible is filled.

4. A method for synthesizing high-density and high-purity silicon carbide according to claim 1, characterized in that: In step 2, the insulation layer arranged in the vacuum synthesis furnace is graphite carbon felt, and the bottom of the graphite carbon felt is provided with an aperture, and the aperture size is 15-20 cm.

5. A method for synthesizing high-density and high-purity silicon carbide according to claim 1, characterized in that: The vacuum pressure in step 2 is 0.5 Pa, and the inert gas is argon.

6. A method for synthesizing high-density and high-purity silicon carbide according to claim 1, characterized in that: In the step three, the first area occupies one quarter of the volume of the crucible, the temperature is controlled at 1950-2100°C, and the insulation time is 18-25H; the second area occupies one quarter of the volume of the crucible, the temperature is controlled at 2100-2200°C, and the insulation time is 18-25H; the third area occupies one quarter of the volume of the crucible, the temperature is controlled at 2150-2200°C, and the insulation time is 18-25H; the fourth area occupies one quarter of the volume of the crucible, the temperature is controlled at 1950-2100°C, and the insulation time is 18-25H.

7. A method for synthesizing high-density and high-purity silicon carbide according to claim 1, characterized in that: The cooling and furnace stopping time in step 4 is 20-30 hours, the particle size of the silicon carbide powder is 0.4 mm and the coarse content is ≥ 75%, and the purity of the silicon carbide powder is above 99.99995%.